Real Exchange Rate of Moroccan Currency: Appreciated or Depreciated? - Lezar, Mohammed Amine (International Journal of Economics and Financial Issues, 2023)
In this paper, we measure and evaluate the real parity of the Moroccan dirham during the period 1980-2020. The objective is to highlight the evolution of the real exchange rate of the dirham, and in particular to show if whether it has been overvalued against currencies of the main trading partners and competitors of Morocco. Contrary to many studies which used a simple method to calculate the real parity which consisted of assigning each country of the main trading partners a relative weight equivalent to its share in Morocco’s external trade, we calculate the weights by combining both bilateral import weights and a double weighting for export to reflect both importance of each country in Morocco’s import and export as well as the degree of competition of exporters in usual third markets. Calculation of real parity of the dirham reveals three main periods: a strong depreciation during 1980-1990; an appreciation during the period 1991-2000; and a resumption of a weaker depreciation for the last period (2001-2020). These trends are related to both changes in nominal effective exchange rate and in relative prices. Results obtained in the present paper are generally close to those calculated by the International Monetary Fund for Morocco and are strongly correlated with them and the trends in both remain the same.